Global Claims in Construction - Haidar, Ali (Springer eBooks., 2011)
Recent years, a number of global claims have failed because they were presented without any systematic analysis, justification or proper calculation of losses. Hence, Global Claims in Construction highlights these issues as well as the importance of understanding causation, factual necessity and the courts? attitude and approach to global claims. Global Claims in Construction addresses the principles of global claims and their calculation methodologies in detail through extensive references to literature, case law and a real world case study. It aims to be a valuable resource for professionals working in the construction industry, as well as students in construction and engineering.